2004
DOI: 10.1177/194589240401800506
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Toxicity of Benzalkonium Chloride

Abstract: BAC in concentrations used in nasal preparations is ciliotoxic. In healthy individuals, the ciliotoxic effect of BAC is neutralized, probably by components of nasal secretions. No BAC-related proinflammatory effects have been observed. At higher doses than normally used therapeutically, BAC caused significant nasal irritation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 53 publications
2
33
0
1
Order By: Relevance
“…Nasal mucus and mucociliary clearance function as a mechanical barrier to protect ciliated nasal epithelium from the detrimental effects of exogenous substances [6,9]. Indeed, a study by Riechelmann et al [7] has recently demonstrated that although BKC was significantly ciliotoxic to human nasal epithelial cells in vitro, this agent did not show any significant ciliotoxic or proinflammatory effects in the nasal mucosa in vivo. The authors suggested that the ciliotoxic effect of BKC in vivo was probably neutralized by components of nasal secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasal mucus and mucociliary clearance function as a mechanical barrier to protect ciliated nasal epithelium from the detrimental effects of exogenous substances [6,9]. Indeed, a study by Riechelmann et al [7] has recently demonstrated that although BKC was significantly ciliotoxic to human nasal epithelial cells in vitro, this agent did not show any significant ciliotoxic or proinflammatory effects in the nasal mucosa in vivo. The authors suggested that the ciliotoxic effect of BKC in vivo was probably neutralized by components of nasal secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, PS is a white crystalline powder, which is used in foods, cosmetics, and drug preparations to inhibit mold, yeast, and bacterial growth. Although a long application history has demonstrated both safety and effectiveness of these two preservatives [6], several studies have demonstrated that BKC impairs the ciliary function of nasal epithelial cells in vitro [7,8,9]. The findings from our present study are in accordance with the findings from other studies employing an in vitro nasal epithelial cell culture model [8,9], and suggest that BKC produces adverse effects on ciliary activity in primary nasal epithelial cell cultures at the concentration commonly used in clinical preparations.…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of preservatives is available but some of them, like phenol, bisulfites, edetate and benzalkonium chloride can cause airway irritation and result in bronchoconstriction or reduce the efficacy of the medicine [57]. Other compounds such as chlorobutanol, methyl-and propyl-parahydroxybenzoate and also benzalkonium chloride are ciliotoxic at concentrations equal to or lower than those in use for preserving aqueous formulations [58,59]. Ciliotoxicity, reduced medicine efficacy and airway irritation resulting in cough and chest tightness are the reasons why many bactericidal agents have been removed now from marketed medicine formulations.…”
Section: Stability Of Formulations For Nebulisationmentioning
confidence: 97%
“…Ряд исследований показал, что нанесение бензалкония хлорида на слизистую оболочку полости носа вызы вает раздражение, гиперсекрецию и замедление му коцилиарного транспорта [28,29]. Ощущение жже ния и явления раздражения в полости носа были значительно сильнее у пациентов, которые получа ли оксиметазолин с добавлением консерванта (бен залкония хлорида), и статистически значимо умень шались у больных, получавших препарат в чистом виде [30][31][32].…”
Section: фармакотерапия заболеваний носа и околоносовых пазух российсunclassified